Environmental Health Risk Analysis of Paraquat Exposure in Palm Oil Plantations - Maksuk Maksuk; Tan Malaka; Suheryanto Suheryanto; Abu Umayah (Intelektual Pustaka Media Utama, 2016)
Paraquat (1, 1’-dimethyl-4, 4’-bipyridylium dichloride) is a highly toxic herbicide. Recently, Paraquat is still used widely in the plantations area, mainly in palm oil plantations. Paraquat application continuously can be increased Paraquat concentration and contaminated in soil and water. This study aimed was to analysis Paraquat exposure in environmental media water and soil, and the calculation of risk quotient of Paraquat in palm oil plantation. The study design of this research was a cross sectional with the laboratory examination Paraquat concentrations in soil and water. Soil and water samples taken by grab sampling with random composites. Water samples were taken from three sources in palm oil plantations area. Whereas soil samples were taken at a depth of 0-10 cm (top soil) and the number of soil samples as much as 5 samples. Furthermore, the risk quotient of Paraquat concentration in the water used in the palm oil plantation. The laboratory tests of Paraquat concentration were in water and soil with gas chromatography. The results of laboratory tests showed that Paraquat concentration in water samples were found between <0.005 to 0.01 mg/l and Paraquat concentration in soil samples were found between <0.005 to 0.08 ppm. The calculation of risk quotient was 0.058 mg/body weight/day. Although, the calculated of risk quotient showed less than one. Therefore, prior to use the water must be treatment first. While the recommended water to consumption as much as 2 liters/day for a 55 kg body weight to Indonesian workers.